Amplified Arctic warming and mid‐latitude weather: new perspectives on emerging connections. (16th May 2017) - Francis, Jennifer A.; Vavrus, Stephen J.; Cohen, Judah
Abstract : The Arctic is warming and melting at alarming rates. Within the lifetime of a Millennial, the volume of ice floating on the Arctic Ocean has declined by at least half. The pace of Arctic warming is two‐to‐three times that of the globe; this disparity reached a new record high during 2016. While the Arctic spans only a small fraction of the Earth, it plays a disproportionate and multifaceted role in the climate system. In this article, we offer new perspectives on ways in which the Arctic's rapid warming may influence weather patterns in heavily populated regions (the mid‐latitudes) of the Northern Hemisphere. Research on this topic has evolved almost as rapidly as the snow and ice have diminished, and while much has been learned, many questions remain. The atmosphere is complex, highly variable, and undergoing a multitude of simultaneous changes, many of which have become apparent only recently. These realities present challenges to robust signal detection and to clear attribution of cause‐and‐effect. In addition to updating the state of this science, we propose an explanation for the varying and intermittent response of mid‐latitude circulation to the rapidly warming Arctic. WIREs Clim Change 2017, 8:e474. doi: 10.1002/wcc.474 This article is categorized under: Climate Models and Modeling > Knowledge Generation with Models Abstract : An unusually warm Arctic during 2016: a preview of a 2°C warmer world? Rapid Arctic warming is expected to affect weather patterns around the Northern Hemisphere, but exactly how, where, and when is a rapidly evolving research topic. The figure shows departures from normal of near‐surface air temperatures (°C) during 2016. Baseline is 1981–2010; data are from the National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) Reanalysis at http://www.esrl.noaa.gov/psd/ .